Risks of Maternal Obesity in Pregnancy: A Case-control Study in a Portuguese Obstetrical Population - Patrícia Alves; Maria Filipa Malheiro; João Cavaco Gomes; Tiago Ferraz; Nuno Montenegro (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2020)
Abstract Objective The present study aims to understand to what extent obesity is related to adversematernal, obstetrical, and neonatal outcomes in a Portuguese obstetrical population. Methods A retrospective case-control study was conducted at the Department of Obstetrics of a differentiated perinatal care facility. The study compared 1,183 obese pregnant womenwith 5,399 normal or underweight pregnantwomen for the occurrence of gestational diabetes, hypertensive pregnancy disorders, and preterm birth. Mode of delivery, birthweight, and neonatal intensive care unit (ICU) admissionswere also evaluated. Mean blood glucose values were evaluated and compared between groups, in the first and second trimesters of pregnancy. Only singleton pregnancies were considered. Results The prevalence of obesity was 13.6%. Obese pregnant women were significantly more likely to have cesarean sections (adjusted odds ratio [aOR] 2.0, p< 0.001), gestational diabetes (aOR 2.14, p< 0.001), hypertensive pregnancy disorders (aOR 3.43, p< 0.001), and large-for-gestational age ormacrosomic infants (aOR 2.13, p< 0.001), and less likely to have small-for-gestational age newborns (aOR 0.51, p< 0.009). No significant differences were found in terms of pretermbirths, fetal/neonatal deaths, low birthweight newborns, and neonatal ICU admissions among cases and controls. Maternal obesity was significantly associated with higher mean blood glucose levels, in the first and second trimesters of pregnancy. Conclusion Obesity is associated with increased risks of adverse pregnancy and neonatal outcomes. These risks seem to increase progressively with increasing body mass index (BMI) class. Female obesity should be considered a major public health issue and has consequences on maternal-fetal health.